Using Information Technology to reduce the risk of Fraud (Applied research in the National Insurance Company) - Assistant lecturer Noor Ali Salman Al-Azawi, Assistant lecturer Zainab Sadiq Ibrahim, (Opción)
The research aims to shed light on information technology in reducing the risk of fraud in the National Insurance Company, that the company’s use of an accurate and sophisticated information system with skill, experience and modernity appropriate to the service provided to customers will enable it to overcome and control the risk of fraud, which is one of the most important and evolving crimes With the passage of time. The development of fraudulent methods and means that the insured uses to inflict the insurance company to pay under the influence of these methods to give the amount of compensation voluntarily.